Content of elections and election legislation in Uzbekistan - Sabokhat Sakanova Muhamedovna; Feruza Matyakubova Ravshanbekovna; Doniyor Otamuratov Madyar Ogli (Universitas Muhammadiyah Sidoarjo, 2019)
In this article it is aimed that to clarify and manifestate the election types and election legislation,also some news which are happening in election system.Besides, here are given some information about the code of elections in the Republic of Uzbekistan.